Non-pharmacological intervention for gastro-oesophageal reflux disease in primary care - Dibley, Lesley B; Norton, Christine; Jones, Roger (British journal of general practice, 2010)
Up to 50% of patients with gastro-oesophageal reflux disease (GORD) have persistent symptoms despite taking proton pump inhibitors (PPIs) regularly. Lifestyle advice is available to patients, but no previous UK study has tested a behavioural change intervention to help patients self-manage their symptoms. To determine whether a primary care, nurse-led intervention to address behaviours that promote GORD symptoms results in symptom improvement, an increased sense of control, and a reduced requirement for prescribed medication. A group intervention focusing on diet and stress was delivered to patients with reflux symptoms, recruited in rural general practices. General practice in England. Forty-two subjects (male 19, female 23) aged 31-86 years took part. Pre- and post-intervention data were gathered using the Brief Illness Perception Questionnaire (BIPQ), the GORD Impact Scale (GIS), and the Hospital Anxiety and Depression Scale (HAD). There was a significant improvement (BIPQ P<0.001, GIS P = 0.008) 3 months after the intervention. There was no reduction in PPI use or change in HAD score. The greatest improvements were demonstrated in domains measuring the patient's sense of control, perception of symptoms, and understanding of reflux. Patients reported benefits including understanding relevant anatomy and physiology, learning behavioural techniques to change eating patterns and manage stress, identifying actual and potential triggers, and developing and executing action plans. An education programme for GORD enhances self-management, brings perceived symptom improvement, and promotes a sense of control at 3 months. This type of behavioural intervention, alongside medical management, could improve symptom control for reflux patients with refractory symptoms and should be the subject of a controlled trial.